T-cell rich B-cell lymphoma of the breast: A rare case report with emphasis on the role of immunohistochemistry in the diagnosis - Sapkota, Sulav; Naik, Radheshyam; Badarke, Girish; Srinivasa, B. J.; Veena, R.; Priyadarshini, Mona; Swamy, Shivakumar (Indian Journal of Case Reports, 2018)
Primary breast lymphoma is one of the rare tumors that commonly presents as a lump with